Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376678
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Movement

Abstract: How is ethics shaped by the particularities of a design? Through a detailed video analysis, we explore how ethicality is shaped in interaction between a choreographer, a performer and a choir of five drones, performing together on the opera stage. We pinpoint how movements enabled by the humandrone assemblage may limit or liberate artistic expressions vis-à-vis the norms of operatic performance. From a somaesthetics perspective on ethics, we show how the process of crafting rich experiences together with drone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Additionally, this suggests that attention should be paid to how are we changing the bodies of those we design for, a question that has ethical implications [18]. Ultimately, our aim as soma design researchers is to expand upon our repertory of somaesthetic experiences, to increase our aesthetic appreciation of ourselves, others and the world around us.…”
Section: Playing Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this suggests that attention should be paid to how are we changing the bodies of those we design for, a question that has ethical implications [18]. Ultimately, our aim as soma design researchers is to expand upon our repertory of somaesthetic experiences, to increase our aesthetic appreciation of ourselves, others and the world around us.…”
Section: Playing Withmentioning
confidence: 99%
“…Rather than articulating touch as an interaction between separate entities with fixed boundaries [15,78,94], we instead consider novel experiences of touch that start from the notion of entanglement of humans and technologies [23,102], akin to correspondence relationships [44] or intra-actions [6], where the technologies are perceived more as an extension of the body than as a separate entity or communication counterpart [37]. We found that the perception of boundaries between human bodies and materials, as well as the perception of who is touching and being touched, was useful to guide the design of wearables for both becoming In a sense, as designers we leave behind a set of "sedimented movements" [18] embedded in the particulars of the designed system that will literally shape users' somas; changing muscles, nervous system reactions, behaviours, experiences, and feelings, and influencing users' capacity for aesthetic appreciation. Hence, when designing, the "materia" being shaped is both the hybrid digital/physical technology, but also the users' somatic selves.…”
mentioning
confidence: 98%
“…The frst is agency, where machines and users can take turns leading the interaction. The second is scale, where machines and humans can be integrated at diferent levels: on the skin (such as wearables) [44,79,82,83], beyond the skin (voice, gesture, ambient and other 'remote' interactions) [19,76] and inside the skin (implanted, edible) [29,48]. This suggests that the boundaries between humans and computers are liminal and open to new challenges and opportunities at the meeting between the two, such as designing bodily prostheses (one of our case studies), or designing for feeling as one with a vehicle when driving.…”
Section: Inside Vs Outsidementioning
confidence: 99%
“…Although embodiment has less focus on data granularity, the impact of making data-driven technologies an extension of our sensory 'system was very visible in the ability to connect to our ethics in movement [39]. In addition, introducing materiality and narratives into the embodied data interactions, such as the global temperature change narrative from Paper 3 or the condensed CO2 narrative from Paper 4, also supports affective engagement.…”
Section: Embodied Data Interactionsmentioning
confidence: 99%